Deregulation factors of business communicative norms in modern English drama texts - A. A. Kharkovskaya; L. M. Leonovich (Дискурс профессиональной коммуникации, 2020)
This article aims at the analysis of the linguistic and paralinguistic aspects of business communicative models in the plays by modern English speaking playwrights. The main methods of the undertaken study are those of functional-linguistic and linguosynergetic analysis. Due to the dialogue structure of plays, the examples of personages’ business interactions could be taken as robust empirical material for business discourse studies and observations of the factors which cause deregulation of business communication and its pragmatic norms. During business-related verbal interaction interlocutors follow strict rules and norms of English business discourse to achieve their communicative goals. However, even the most regulated speech behavior could be affected by functional and stylistic fluctuations due to unpredictability of extralinguistic factors. Analysis of extensive empirical material proves that the functional framework of business communicative norms in personages’ speech behavior is regulated by the speaker’s personality, psychology and emotional state, background knowledge as well as multiple elements of the external environment of the discursive functional system. The communicative strategies of drama characters are reflected in their choice of linguistic and paralinguistic methods of pragmatic impact on the interlocutor’s mind.